Ferroptosis in thyroid cancer: mechanisms, current status, and treatment - Tian, Wenzhi; Su, Xi; Hu, Chenchen; Chen, Dong; Li, Peng (Frontiers in Oncology, 2025)
Thyroid cancer (TC) represents the most prevalent malignancy within the endocrine system. In recent years, there has been a marked global increase in the incidence of thyroid cancer, garnering substantial scientific interest. Comprehensive investigations into the pathogenesis of TC have identified a significant association with ferroptosis, a newly characterized form of cell death mediated by iron ions. Distinct from apoptosis, necrosis, and autophagy, ferroptosis is characterized by the accumulation of lipid peroxides and reactive oxygen species, culminating in cellular damage and death.Recent research has elucidated a connection between ferroptosis and the initiation, progression, and treatment of thyroid cancer. These findings underscore the significance of ferroptosis in thyroid cancer and offer valuable insights into the development of novel therapeutic strategies and precise predictive markers. The unique mechanisms of ferroptosis present opportunities for targeting treatment-resistant thyroid cancers. Consequently, the regulation of ferroptosis may emerge as a novel therapeutic target, potentially addressing the limitations of current treatments. Moreover, elucidating the molecular mechanisms underpinning ferroptosis in thyroid cancer may facilitate the identification of novel biomarkers for early detection and prognostication. This review endeavors to synthesize the extant knowledge regarding the role of ferroptosis in thyroid cancer, examine potential therapeutic implications, and propose future research trajectories to enhance the understanding and clinical application of ferroptosis.